The Role of Critical Thinking Skills in Enhancing Scientific Literacy in Chemistry : A Systematic Literature Review - Amna Utyta; Habiddin; Yahmin (Jurnal Pendidikan Kimia FKIP Universitas Halu Oleo, 2025)
Chemistry learning often faces obstacles due to its abstract concepts, which are difficult to observe directly. As a result, students tend to rely on memorization rather than understanding molecular mechanisms and practical applications. This study is a Systematic Literature Review (SLR) using the PRISMA protocol to map the role of critical thinking skills in enhancing science literacy. From 425 articles (2018–2025), 20 studies were thematically analyzed. Five effective active learning strategies were identified: Argument-Driven Inquiry (ADI), Inquiry-Based Learning (IBL), Problem-/Project-Based Learning (PBL/PjBL), integration of Socio-Scientific Issues (SSI) with Augmented Reality (AR), and reflective journaling. These approaches have been shown to improve students’ abilities in analysis, evaluation, and synthesis of information, while also promoting knowledge transfer to real-world contexts. Recommendations include the development of hybrid modules integrating argumentation, guided experiments, contextual discussions, and metacognitive reflection, as well as the need for standardized assessment instruments and further experimental studies across educational levels and cultural settings